INTEGRATION OF UKRAINE INTO THE EUROPEAN EDUCATION SYSTEM AT THE BEGINNING OF THE 21ST CENTURY THROUGH THE PRISM OF COLLABORATION WITH THE EUROPEAN TRAINING FOUNDATION - ALEXIYEVETS, Lesya; PETRYK, Tetiana; PETRYK, Yurii (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2023)
The article highlights Ukraine's cooperation with the European Training Foundation at the beginning of the 21st century. The importance of Ukraine's integration into the structures of the European Union through active participation in the programs of the European Training Foundation was noted, as Ukraine is on the way to the European Union and has acquired the status of a candidate country for membership in the European Union. The projects that were implemented in cooperation between the Ministry of Education and Science of Ukraine and the European Training Foundation are described. Cooperation is based on such areas as lifelong learning, development of professional skills and qualifications, analysis of the need for professional skills and employment, training in entrepreneurship and key competencies, improving the quality of professional education, system management and financing, participation in the Turin process. Among the projects implemented during the years 2011-2020 are «Improving the system of vocational and technical education by forecasting and adapting skills and abilities, social partnership and optimizing the use of resources» (2011–2013), «PRIME: forecasting the impact of reforms in the field of vocational education and training of workers» (2014–2015), «On-the-job training» (2015–2017), «Decentralization of vocational and technical education in Ukraine – impetus for action» (2016), «Public-private partnership in the development of professional education» (2018–2019), «Increasing the effectiveness of regional VET networks: joint work on the creation of Centers of professional excellence in Ukraine» (2019), «Reforming regional networks of professional (professional and technical) education in Ukraine: introduction of autonomy and reporting of professional (professional and technical) education institutions» (2019–2020). Highlighted the main aspects of these projects, analyzed their essential components, examined key aspects of project implementation, and scrutinized the fundamental components within their structure. The peculiarities of the implementation of the mentioned projects in the context of cooperation between the European Education Fund and the Ministry of Education and Science of Ukraine have been clarified. The role of the cooperation of the Ministry of Education and Science of Ukraine with the European Training Foundation as an important factor for the Ukraine integration into the European education system was considered, and the prospects of this cooperation were determined.